2021
DOI: 10.1002/jbm.b.34931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bioactive glasses containing strontium and potassium on dentin permeability

Abstract: Dentin hypersensitivity (DH) is characterized by pain caused by an external stimulus on exposed dentin. Different therapeutic approaches have been proposed to mitigate this problem; however, none of them provide permanent pain relief. In this study, we synthesized and characterized experimental bioactive glasses containing 3.07 mol% SrO or 3.36 mol% K 2 O (both equivalent to 5 wt% in the glass), and evaluated their effect on dentin permeability to verify their potential to treat DH. The experimental materials … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Many researchers have doped BG with various ions to enhance the beneficial nature of BG 12 . Therapeutic inorganic ions such as iron (Fe), 13 copper (Cu), 14 zinc (Zn), 15 strontium (Sr), 16 gallium (Ga), 17 and cerium (Ce) 18 are considered to be suitable bioactive dopants, which replace the Ca or P sites in the network 19–20 . Even co‐doping of inorganic ions (Co, Mg or Zn) into the BG network has been performed to achieve multiple beneficial functions 16,21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have doped BG with various ions to enhance the beneficial nature of BG 12 . Therapeutic inorganic ions such as iron (Fe), 13 copper (Cu), 14 zinc (Zn), 15 strontium (Sr), 16 gallium (Ga), 17 and cerium (Ce) 18 are considered to be suitable bioactive dopants, which replace the Ca or P sites in the network 19–20 . Even co‐doping of inorganic ions (Co, Mg or Zn) into the BG network has been performed to achieve multiple beneficial functions 16,21 …”
Section: Introductionmentioning
confidence: 99%
“…12 Therapeutic inorganic ions such as iron (Fe), 13 copper (Cu), 14 zinc (Zn), 15 strontium (Sr), 16 gallium (Ga), 17 and cerium (Ce) 18 are considered to be suitable bioactive dopants, which replace the Ca or P sites in the network. [19][20] Even co-doping of inorganic ions (Co, Mg or Zn) into the BG network has been performed to achieve multiple beneficial functions. 16,21 To incorporate metal cations into BG, melt-quenching, sol-gel and ion-exchange are the common strategies using a direct mixture of metallic salts 12 or their oxides 18 with precursors of glass composition.…”
mentioning
confidence: 99%
“…Numerous studies have demonstrated that BAG can combine with a suitable carrier to stimulate apatite formation in dentin [140][141][142]. Table 3 summarizes the studies on BAG fillers in remineralizing the resindentin bonding interface and improving the mechanical properties.…”
Section: Effect Of Bag Fillers On the Remineralization And Mechanical...mentioning
confidence: 99%